2005
DOI: 10.1088/0953-4075/38/10/006
|View full text |Cite
|
Sign up to set email alerts
|

The dissociative recombination of fluorocarbon ions: II. CF+

Abstract: The dissociative recombination and excitation of CF+ have been measured at the ASTRID and CRYRING storage rings. Though examination of the available potential energy curves would suggest that the recombination rate would be large for this ion, in fact a rate constant of 5.2 ± 1.0 × 10−8 (Te/300)−0.8 cm3 s−1 was found. The recombination cross section at low energies falls off to a minimum at 0.5 eV centre-of-mass collision energy but exhibits resonances at energies above this. The dissociative excitation cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…It has been shown, however, that DR rate coefficients of diatomics can differ by large factors from alleged typical values. For example, for CF + Novotny et al (2005) measured a rate coefficient a factor of 4 lower than that commonly taken for the typical diatomic ion value. For this reason Neufeld et al (2012) have identified the DR rate coefficient of HCl + as an "urgently needed" parameter significantly affecting the uncertainty of chlorine-chemistry models.…”
Section: Introductionmentioning
confidence: 79%
“…It has been shown, however, that DR rate coefficients of diatomics can differ by large factors from alleged typical values. For example, for CF + Novotny et al (2005) measured a rate coefficient a factor of 4 lower than that commonly taken for the typical diatomic ion value. For this reason Neufeld et al (2012) have identified the DR rate coefficient of HCl + as an "urgently needed" parameter significantly affecting the uncertainty of chlorine-chemistry models.…”
Section: Introductionmentioning
confidence: 79%
“…Where no reliable DR data exist for diatomic molecules, astrochemical models commonly assume a "typical" rate coefficient of α di pl ≈ 2.0×10 −7 ×(300/T ) 0.5 cm 3 s −1 (Florescu- Mitchell & Mitchell 2006). As has been shown for CF + (Novotny et al 2005) and HCl + (Novotný et al 2013), α di pl does a poor job of matching experimentally derived rate coefficient α pl both in magnitude and temperature dependence. Taking the ratio of our new DR results to that commonly assumed we find α pl /α di pl = 1.9, 1.2, 0.9, 0.6, and 0.5 at T = 10, 30, 100, 300, and 1000 K, respectively.…”
Section: Plasma Rate Coefficientmentioning
confidence: 90%
“…The reactions rates are k 1 = 7.2 × 10 −9 (T/300) −0.15 cm 3 s −1 (Neufeld et al 2005) and k 2 = 5.3 × 10 −8 (T/300) −0.8 cm 3 s −1 (Novotny et al 2005). The CF + photodissociation rate k pd is not known.…”
Section: Cfmentioning
confidence: 99%